Kinetically Controlled Synthesis of Four‐ and Six‐Member Cyclic Products via Sequential Aryl‐Aryl Coupling on a Au(111) Surface. Issue 18 (28th May 2019) - Zhang, Ran; Xia, Bowen; Xu, Hu; Lin, Nian
Abstract: We synthesize four‐ and six‐member cyclic products via sequential multi‐step aryl‐aryl coupling reactions of 2, 3, 6, 7, 10, 11‐hexabromotriphenylene molecules on a Au(111) surface. The final products as well as the organo‐gold intermediate structures are identified using scanning tunneling microscopy and density‐functional theory simulation. By adjusting reaction temperature and post‐annealing temperature, we enhance/suppress the yields of the four‐member and six‐member cyclic products. We propose an underlying mechanism which is associated with different reaction kinetics of the first‐order and second‐order reactions. This work exemplifies intricate kinetically‐controlled on‐surface synthesis when multiple reactions of different reaction order are involved. Abstract : Multi‐step aryl‐aryl coupling reactions of 2, 3, 6, 7, 10, 11‐hexabromotriphenylene molecules on Au(111) are reported. The products are characterized by STM.